How Long Can a Dead Body Remain Infectious?: Postmortem Nasopharyngeal Swabs and SARS-CoV-2 Culture in a Corpse Over an 87-Day Period. (7th September 2022) - Ventura, Francesco; Drommi, Martina; Barranco, Rosario; Balbo, Arianna; Errico, Stefano; Mangioni, Manuela; Molinari, Giulia; Di Biagio, Antonio; De Pace, Vanessa; Lai, Alessia; Bruzzone, Bianca
Abstract: The SARS-CoV-2 pandemic involved several changes and difficulties in the work of forensic pathologists. Postmortem nasopharyngeal swabs for the diagnosis of the SARS-CoV-2 infection are recommended before an autopsy examination by the Centers for Disease Control and Prevention. Autopsy examinations must not be performed for SARS-CoV-2 infection cases when airborne infection isolation rooms or other suitable spaces are unavailable. However, it has not yet been reported whether the presence of SARS-CoV-2 at a low viral load may be enough to infect and disseminate the contagion. Here, we report the case of a 67-year-old man found dead at home on November 9, 2020, and transferred immediately after to the Genova District Mortuary. As the first postmortem molecular nasopharyngeal swab resulted positive, a weekly sampling was carried until February 4, 2021. All the molecular tests were positive for SARS-CoV-2, including the last swab performed 87 days after the arrival of the corpse at the morgue. Virus isolation conducted on VERO E6 cells revealed no cytopathic effect indicating no viral replication as early as 18 days after the corpse's arrival at the morgue and until January 2021. Our findings suggest that the presence of the genome of SARS-CoV-2 at low viral load should not be considered a sign of an active infection but a trace of a remaining viral genome from a previous infection. Then, if the virus shows no replication activity, its molecular detection should not constitute a threat to public health. Further studies are required to establish the infection's potential and its correlation with viral load.